2014
DOI: 10.3354/cr01255
|View full text |Cite
|
Sign up to set email alerts
|

Evaporation trends in Spain: a comparison of Class A pan and Piché atmometer measurements

Abstract: Interest is growing in the trends of atmospheric evaporation demand, increasing the need for long-term time series. This work describes, for the first time, the development of a dataset on evaporation in Spain based on long-term series of Piché and pan measurement records. Piché measurements have been reported for > 50 stations since the 1960s. Measurements of pan evaporation, which is a much more widely studied variable in the literature, are also available, but only since 1984 for 21 stations. Particular emp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 42 publications
1
5
0
4
Order By: Relevance
“…The underestimation partly could be due to lack of sufficient wind in the Stevenson's screen that was shielding the evaporimeter Sanchez-Lorenzo et al (2014). These underestimations of the ETo results were similar to those of Diop et al (2015), but different from those of Knox et al (2011) who observed overestimation of ETo relative to FAO56-PM.…”
Section: Comparison Of Eto Estimates Of the Penmanmonteith Methods Andsupporting
confidence: 68%
See 2 more Smart Citations
“…The underestimation partly could be due to lack of sufficient wind in the Stevenson's screen that was shielding the evaporimeter Sanchez-Lorenzo et al (2014). These underestimations of the ETo results were similar to those of Diop et al (2015), but different from those of Knox et al (2011) who observed overestimation of ETo relative to FAO56-PM.…”
Section: Comparison Of Eto Estimates Of the Penmanmonteith Methods Andsupporting
confidence: 68%
“…However, the Class A pan had the least MAE and MAPE (0.26 mm day -1 and 6.5% respectively) relative to the Piche evaporimeter and even among all the methods. The difference in their correlation coefficients and the errors could be due to the fact that the Piche evaporimeter was shielded from solar radiation and its measurement could not be directly affected by the radiative parameters controlling ETo which was not the case for the Class A pan which was in the open as intimated by Sanchez-Lorenzo et al (2014).…”
Section: Degree Of Agreement Between Eto-pm and Eto Estimated By The mentioning
confidence: 99%
See 1 more Smart Citation
“…The use of methods for calculating ET o requiring only temperature data, such as the Thornthwaite (Thornthwaite, 1948) or Hargreaves (Hargreaves and Samani, 1985) approaches, are still common, especially because temperature is commonly available, and temperature and solar radiation accounts for 80 % of the ET o variability (Mendicino and Senatore, 2013;Samani, 2000). One of the major drawbacks of these methods is that variability and trends in the estimated ET o values depend only on temperature, regardless of the importance of the other variables (Irmak et al, 2012;McVicar et al, 2012;Sheffield et al, 2012;Tomas-Burguera et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…They also found that ETo trends were mainly explained by the decrease in relative humidity and the increase in maximum temperature since the 1960s, particularly during summer months. Sánchez-Lorenzo et al (2014) developed, for the first time, an evaporation dataset for Spain based on long-term series of Piché atmometer and pan measurement records. Both the mean annual Piché and pan series showed evaporative increases over Spain during the study period (1985−2011).…”
Section: The Atmospheric Evaporative Demandmentioning
confidence: 99%